Visual sensitivity and spatial resolution of the planktivorous fish, Atherinomorus forskalii (Atherinidae; Rüppell, 1838), to a polarized grating. (February 2017) - Lerner, Amit; Shmulevitz, Ron; Browman, Howard I.; Shashar, Nadav
Abstract: Polarized light detection has been documented in only a small number of fish species. The benefit of polarization vision for fish is not fully understood, nor is the transduction mechanism that underlies it. Past studies proposed that one possible advantage of polarization vision is that it enhances the contrast of zooplankton targets by breaking their transparency. Here, we used an optomotor apparatus to test the responses of the planktivorous Hardyhead silverside fish Atherinomorus forskalii (Atherinidae) to vertical unpolarized (intensity) and polarized gratings. We also tested and compared the spatial and temporal resolutions of A. forskalii in the intensity and polarization domains. A. forskalii responded to the polarization pattern, but only under illumination that included ultraviolet-blue (λ > 380 nm) wavelengths. The spatial resolution of A. forskalii was measured as a minimum separable angle of 0.57° (a 1-mm prey viewed from 100-mm distance). The temporal resolution to unpolarized vs. polarized gratings was constant, at 33 and 10 Hz respectively at most of the stripe widths tested. At the smallest stripe width tested (1 mm = the minimal separable angle), which correlates with the size of prey typically consumed by these fish, the temporal resolution to the polarized grating increased to 42 Hz. We conclude that A. forskalii is polarization sensitive, may use polarization vision to improve detection of its planktonic prey, and that polarization may be perceived by the fish via a separate visual pathway than intensity.